IMPLEMENTASI ARTIFICIAL INTELLIGENCE UNTUK MENINGKATKAN INOVASI PEMBELAJARAN PADA SMPN 1 PAGEDANGAN - Rafli Adi Prasetya; Dwi Agung Septian; Muhamad Rafli Harahap; Handika Duwi Purnomo; Farhat Adriansyah; Dewa Pragusha; Rangga Maulana; Maulana Ichsan; Mohd. Zacky Bharya; Oki Ahmad Fauzi; Jiyan Suhada (Abdi Jurnal Publikasi, 2025)
This community service activity aims to enhance innovation in the learning process by utilizing Artificial Intelligence (AI) technology at SMPN 1 Pagedangan. In today's digital era, the use of AI in education offers a more personalized, adaptive, and interactive learning experience. However, the understanding of this technology among teachers and students remains relatively low. Therefore, through this program, the community service team conducted a series of activities including workshops, training, and mentoring sessions designed to introduce the basic concepts of AI and its application in the educational context. The materials presented covered topics such as AI fundamentals, the creation of simple educational chatbots, and the use of AI-powered applications to support teaching and learning processes. The implementation method combined both theoretical and practical approaches in an interactive format. The results indicated an improvement in the participants' understanding and enthusiasm towards AI technology. Additionally, participants were able to apply AI in simple forms to support daily classroom learning activities. This initiative not only provided new knowledge but also improved digital literacy and encouraged innovation in learning methods. The program is expected to serve as an initial implementation model for other schools in adopting AI in education. Thus, the use of AI can be further expanded and optimized to support the transformation of education in the digital age